Towards a Cost-Effective Implementation of Genomic Prediction Based on Low Coverage Whole Genome Sequencing in Dezhou Donkey - Zhao, Changheng; Teng, Jun; Zhang, Xinhao; Wang, Dan; Zhang, Xinyi; Li, Shiyin; Jiang, Xin; Li, Haijing; Ning, Chao; Zhang, Qin (Frontiers in Genetics, 2021)
Low coverage whole genome sequencing is a low-cost genotyping technology. Combined with genotype imputation approaches, it is likely to become a critical component of cost-effective genomic selection programs in agricultural livestock. Here, we used the low coverage sequence data of 617 Dezhou donkeys to investigate the performance of genotype imputation for low coverage whole genome sequence data and genomic prediction based on the imputed genotype data. The specific aims were: (i) to measure the accuracy of genotype imputation under different sequencing depths, sample sizes, minor allele frequency (MAFs), and imputation pipelines; and (ii) to assess the accuracy of genomic prediction under different marker densities derived from the imputed sequence data, different strategies for constructing the genomic relationship matrixes, and single- vs multi-trait models. We found that a high imputation accuracy (> 0.95) can be achieved for sequence data with sequencing depth as low as 1x and the number of sequenced individuals ≥ 400. For genomic prediction, the best performance was obtained by using a marker density of 410K and a G matrix constructed using expected marker dosages. Multi-trait GBLUP performed better than single-trait GBLUP. Our study demonstrates that low coverage whole genome sequencing would be a cost-effective approach for genomic prediction in Dezhou Donkey.